PEMBINAAN KERUKUNAN UMAT BERAGAMA MASYARAKAT TRANSMIGRAN DI KALIMANTAN TENGAH - Mukhtar uddin (Analisa: Journal of Social Science and Religion, 2008)
Indonesia is plural society. This pluralism is observed in itsethnics, religions, languages, and customs. In social life, pluralism in religion especially often creates many problems. This couldhappen in migrant society. It is, for example, effected byinterpretation of each religious moral; although in their religion also suggest tolerance.Hence, government needs to manage trans-migrant society. This management could be observed in management administration.Result of the study show that governmental management generallyonly gives religious community's harmony at the beginning of theirsettlement in trans-migrant areas. Afterward, management is doingby religious figures and communities figures. That management isnot specifically designed to manage community in harmony amongreligious community in that area. The management is throughpengajian, religious preaches and lecturers,